A Natural Language Instructor for pedestrian navigation based in generation by selection - Avalos Ambroggio, Santiago Eugenio (2014)
Ponencia presentada en la 14th Conference of the European Chapter of the Association for Computational Linguistics. Workshop on Dialogue in Motion. Gotemburgo, Suecia, 26 de abril de 2014.